Potensi Hijauan Pakan Perkebunan Kelapa Sawit untuk Pengembangan Sapi di Kecamatan Kaliorang Kabupaten Kutai Timur: Study on the Potential of Forage Resources in Oil Palm Plantations for Cattle Development in Kaliorang, East Kutai Regency (Jurnal Ilmu Nutrisi dan Teknologi Pakan, 2026)
This study aims to examine the potential of forage crops in oil palm plantations for cattle maintenance in Kaliorang District, East Kutai Regency. The research method uses an exploratory survey with a quantitative descriptive approach, using a 1 m² plot sampling technique. The design employed is a Randomized Complete Block Design (RCBD) with 3 treatments based on oil palm age (3, 6, and 10 years) and three replications per group. The study identified 90 plant species from 41 families, with Poaceae and Asteraceae being the most dominant families. Paspalum conjugatum showed the highest density (16,617 individuals) and dominance, as measured by the Important Value Index (IVI), across all age groups: 65.89% (3 years), 30.81% (6 years), and 64.23% (10 years). The highest forage production was observed in 3-year-old plantations (9,789.32 kg ha-1), decreasing sharply with increasing plantation age. Cattle carrying capacity followed the forage production pattern, with the highest value of 1.37 Au ha-1 (3 years) and the lowest of 0.30 Au ha-1 (10 years). The study concludes that young oil palm plantations (3 years old) have optimal potential as cattle forage sources but require special management in older plantations to maintain productivity. The oil palm-cattle integration system in the study area should consider plantation age, availability of supplementary feed, and ecological sustainability.